Construction of Hierarchical CuCo2O4-Ni(OH)2 Core-Shell Nanowire Arrays for High-Performance Pseudocapacitors - Azmy*, Ilham; Wang, Jun (Aceh International Journal of Science and Technology, 2022)
The hierarchical CuCo2O4-Ni(OH)2 core-shell nanowire arrays on Ni foam were fabricated using facile and cost-effective two-step hydrothermal synthesis. The growth of CuCo2O4 nanowires was developed on Ni foam as the apposite basis of the conductive scaffold, and the ultrathin Ni(OH)2 nanowires were subsequently immobilized to form CuCo2O4-Ni(OH)2 core-shell nanowire arrays (NWAs). The prepared materials were further characterized in structural, morphological, and electrochemical properties. The obtained CuCo2O4-Ni(OH)2 pseudocapacitor electrode, incorporated by unique core-shell heterostructures nanowire arrays, exhibited great specific capacitance of 1201.67 F g-1 at 1 mA g-1, which is much higher than pristine CuCo2O4 nanowire of 638.89 F g-1 at 1 mA g-1 . Simultaneously, it also has a high power density of 5.56 kW kg-1 at an energy density of 73.33 Wh kg-1 and good long-term cycling performance (~84 capacitance retention after 1000 cycles). The improved morphological and structural properties have substantiated the CuCo2O4- Ni(OH)2 core-shell nanowire arrays properties owing to higher surface active area and richer redox activity for boosting the electrochemical properties.